2018
DOI: 10.1007/s00167-018-5247-1
|View full text |Cite
|
Sign up to set email alerts
|

High performance of critical shoulder angle for diagnosing rotator cuff tears on radiographs

Abstract: PurposePrevious studies have reported that a high critical shoulder angle (CSA) is associated with rotator cuff tears (RCTs). However, the available evidence concerning the strength of the association of these parameters with the pathogenesis of RCTs is conflicting. The aim in the present meta‐analysis was to assess the diagnostic performance of CSA for detecting RCTs. MethodsThe PubMed and EMBASE databases were searched for diagnostic accuracy studies of CSA for detecting RCT. Quality of the included studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The clinical implications of our results are that the CSA and AI measures should be questioned as important prognostic factors for the development of RCT or GH OA and that lateral acromioplasty probably does not prevent RCT’s as suggested [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 87%
“…The clinical implications of our results are that the CSA and AI measures should be questioned as important prognostic factors for the development of RCT or GH OA and that lateral acromioplasty probably does not prevent RCT’s as suggested [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 87%
“…Pandey et al [ 30 ] reported that higher CSAs are associated with a full-thickness tear but not with partial tears. A meta-regression analysis revealed that the sensitivity of CSA could be higher for differentiating full-thickness RCTs and normal patients [ 9 ]. However, another study reported that the mean CSA in patients with full-thickness tears was 34.3 ± 4.2° and those with partial-thickness tears was 32.6 ± 3.2° ( p = 0.08) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between degenerative RCTs and the CSA has recently received increasing attention [ 8 , 9 ]. The CSA, first mentioned in RCT research in 2013 by Moor et al [ 10 ], is defined as the angle between the superior and inferior bony margin of the glenoid and the lateral margin of the acromion (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The acromial morphology has been identified as one of the important etiologic factors of degenerative RCTs [6][7][8]. Numerous studies have revealed that a type III acromion, higher acromion index, lower lateral acromion angles, and larger critical shoulder angles (CSAs) are significantly associated with degenerative RCTs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%